Training by controlling the resistance arms of rubber ropes and their effects on transferring momentum between body parts for the skill of serving in tennis (The International Journal for Scientific Research, 2026)
The skill of serving in tennis is one of the most important skills that the player relies on to achieve victory. It is the starting point for each round and allows the player to control the course of the game. Therefore, players and coaches constantly seek to develop and improve this skill.Recent years have witnessed a great development in training methods for serving, as many modern tools and devices have been used to help players achieve the best performance. Among these tools, rubber ropes stand out as an effective and versatile tool and are characterized by their ability to provide variable resistance, allowing players to train the muscles used in serving effectively. They also help improve neuromuscular coordination and increase the range of motion, which is positively reflected in the player's performance. Therefore, the researchers prepared a new training method using rubber ropes during skill performance and controlling the resistance arms by changing them during training with the aim of improving angular muscle work and giving the body parts angular kinetic momentum so that the serve would be at the highest speed and impact on the competitor. The research was implemented on a sample of (7) young tennis players and the tennis skill was analyzed to extract the biomechanical variables by conducting a pre-test. The sample was applied to the torque and rope training for (8) weeks at a rate of three units per week, which were conducted after the completion of the post-tests. The results of the research included improving the momentum transfer index between the body parts contributing to the performance, improving the angular and circumferential speed of these parts, and improving the speed of the ball’s launch. Providing coaches and players with useful information on how to use these ropes according to the torque principle to improve performance and reach the highest levels.
Keywords: Resistance Arms; Tennis, Serve; kinetic Momentum; Moments; EMG